The crassipalpis species group of the genus Geodromicus Redtenbacher, 1857 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2019)
The crassipalpis species group of the genus Geodromicus Redtenbacher, 1857 is established. Three species of the group from the East Palaearctic Region, including G. crassipalpis Champion, 1920 (India: Uttarakhand), G. amplissimus Shavrin, sp.n. (China: Sichuan, Yunnan), and G. spadiceus Shavrin, sp.n. (Central Nepal) are (re-)described and illustrated. A lectotype is designated for G. crassipalpis. A key to species and distribution maps are provided. [Zoobank URL: http://zoobank.org/urn:lsid:zoobank.org:act:AEA23DBB-1CED-43AD-BC02-8FF196E70D37]